EFEKTIVITAS PEMBELAJARAN AIK DENGAN METODE PROBLEM BASED LEARNING (PBL) DI UNIVERSITAS SAINTEK MUHAMMADIYAH - Ikhsan Hakim (LPPM Universitas Cipta Mandiri, 2024)
This study aims to examine the effectiveness of learning Al-Islam and Muhammadiyah Studies (AIK) using the Problem Based Learning (PBL) method at Universitas Saintek Muhammadiyah. The background of this research arises from the need to implement a learning model that encourages active student participation in understanding AIK values contextually and applicatively. The research method employed was descriptive quantitative, involving 20 students enrolled in the AIK course during the odd semester of the 2024/2025 academic year. Data were collected through learning evaluation questionnaires and classroom observation. The results showed that the application of PBL enhanced students’ engagement in discussions, strengthened their understanding of AIK values, and fostered critical and collaborative thinking skills. Most students stated that PBL made learning more meaningful compared to conventional methods. Therefore, it can be concluded that the implementation of PBL in AIK learning is effective in improving students’ understanding, social skills, and learning motivation.